Sit and face the world: ontogenetic adaptation in infant vocal production and visual attention during the transition to independent sitting - Laudańska, Zuzanna; Malinowska-Korczak, Anna; Babis, Karolina; Mąka, Szymon; Lozano, Itziar; Marschik, Peter B.; Marschik, Dajie; Patsis, Katerina; Szmytke, Magdalena; Podstolak, Monika; Araszkiewicz, Weronika; Tomalski, Przemysław (BMC Psychology, 2025)
Motor milestones are not only indicators of developmental progress, but they also open up new opportunities for infants to interact with the environment and social partners, as the development of motor, social, and language skills is tightly interconnected in infancy. This study will investigate how the transition to independent sitting relates to key areas of socio-communicative development in infancy: vocal production and visual attention.